Photodynamic Action of Curcumin and Methylene Blue against Bacteria and SARS-CoV-2-A Review - Siu Kan Law; Albert Wing Nang Leung; Chuanshan Xu (MDPI AG, 2023)
Coronavirus disease 19 (COVID-19) has occurred for more than four years, and the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing COVID-19 is a strain of coronavirus, which presents high rates of morbidity around the world. Up to the present date, there are no therapeutics that can avert this form of illness, and photodynamic therapy (PDT) may be an alternative approach against SARS-CoV-2. Curcumin and methylene blue have been approved and used in clinical practices as a photosensitizer in PDT for a long time with their anti-viral properties and for disinfection through photo-inactivated SARS-CoV-2. Previously, curcumin and methylene blue with antibacterial properties have been used against Gram-positive bacteria, Staphylococcus aureus (S. aureus), and Gram-negative bacteria, Escherichia coli (E. coli), Enterococcus faecalis (E. faecalis), and Pseudomonas aeruginosa (P. aeruginosa). Methods: To conduct a literature review, nine electronic databases were researched, such as WanFang Data, PubMed, Science Direct, Scopus, Web of Science, Springer Link, SciFinder, and China National Knowledge Infrastructure (CNKI), without any regard to language constraints. In vitro and in vivo studies were included that evaluated the effect of PDT mediated via curcumin or methylene blue to combat bacteria and SARS-CoV-2. All eligible studies were analyzed and summarized in this review. Results: Curcumin and methylene blue inhibited the replication of SARS-CoV-2. The reactive oxygen species (ROS) are generated during the treatment of PDT with curcumin and methylene blue to prevent the attachment of SARS-CoV-2 on the ACE2 receptor and damage to the nucleic acids either DNA or RNA. It also modulates pro-inflammatory cytokines and attenuates the clotting effects of the host response. Conclusion: The photodynamic action of curcumin and methylene blue provides a possible approach against bacteria and SARS-CoV-2 infection because they act as non-toxic photosensitizers in PDT with an antibacterial effect, anti-viral properties, and disinfection functions.